2011
DOI: 10.3747/pdi.2010.00164
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Reduces High Glucose Toxicity in Rat Peritoneal Mesothelial Cells

Abstract: The present study shows that high glucose may promote oxidative stress and may activate apoptotic pathways in rat PMCs. These toxic effects could be reversed by atorvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, the benefits of PD are short-lived, due mainly to morphological and functional alterations of the peritoneum caused by HG PDFs. There is substantial evidence to support HG PDFs cause deterioration of the peritoneum, including an increase in oxidative stress injury and apoptosis in PMCs [11,12]. In this study, it is demonstrated that HG PDFs induce rat PMCs apoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, the benefits of PD are short-lived, due mainly to morphological and functional alterations of the peritoneum caused by HG PDFs. There is substantial evidence to support HG PDFs cause deterioration of the peritoneum, including an increase in oxidative stress injury and apoptosis in PMCs [11,12]. In this study, it is demonstrated that HG PDFs induce rat PMCs apoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…Rat PMCs were isolated from the peritoneum of rats by enzymatic digestion as previously described [33]. To identify PMCs, the cells were examined for specific markers and morphology as described elsewhere [33].…”
Section: Methodsmentioning
confidence: 99%
“…To identify PMCs, the cells were examined for specific markers and morphology as described elsewhere [33]. Cells between passages 3 and 6 were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, statins are safe in high-risk PD patients and display anti-inflammatory effects reflected in reduced serum CRP levels together with the conventional lipid-lowering effect [ 239 ]. In rat and human peritoneal mesothelial cells cultured under high glucose conditions or high glucose-PDF exposition, statins (fluvastatin, atorvastatin, or simvastatin) are protective by modulating the serum- and glucocorticoid-inducible kinase 1 (SGK1) or phospho-p38 MAPK pathways, thus inhibiting the production of growth factors and preventing MMT [ 240 , 241 , 242 ]. In rat PDF exposure models, atorvastatin preserved ultrafiltration and decreased protein loss and PM thickness [ 243 ] and simvastatin restored MMT-induced changes such as those observed in E-cadherin, α-SMA, Snail, and fibronectin expression [ 241 ].…”
Section: Pharmacological Interference With the Th17 Immune Responsmentioning
confidence: 99%